Interação de um aluno com paralisia cerebral com colegas de classe durante atividades ludicas - Pasculli, Adriane Guzman [UNESP]; Baleotti, Luciana Ramos [UNESP]; Omote, Sadao [UNESP] (FapUNIFESP (SciELO), 2012)
The study aimed to examine the quality of interpersonal relationships developed between a child with cerebral palsy (CP) and his classmates during group play activities carried out in the classroom and during recess. The participants of the study were a boy with clinical diagnosis of quadriplegic CP, his teacher and classmates. Data collection was carried out by means of a structured interview with the teacher and of video recording the child with CP interacting with his classmates in play activities. The interview data analysis was carried out using qualitative procedures and the video recording was analyzed using a category system. The results showed that the teacher perceived the child with CP to be interested; he participated in play activities and interacted successfully both with familiar partners and with all classmates in general. On the other hand, the analysis of the video recorded activities showed that even though interaction did in fact occur positively, the child with CP remained mostly an observer of the activities rather than an active participant, possibly due to the gap between the child's possibilities and the requirements imposed by the activities underway in the school setting.
Interaction of a student with cerebral palsy with classmates during play activities
Keywords: Cerebral palsy; Social interaction; Special education; Student participation